Efficacy of Pericapsular Nerve Group (PENG) block in preoperative rehabilitation (Prehabilitation) for patients with femoral neck fractures: study protocol for a randomized, placebo-controlled, double-blinded trial - Zhuan Jin; Daisuke Sugiyama; Fumiya Higo; Takahiro Hirata; Osamu Kobayashi; Hiroshi Morimatsu; Kenichi Ueda (BMC Anesthesiology)
Abstract Background Despite surgery intervention for femoral neck fractures is recommended within 48 h of admission, achieving timely surgery presents challenges for patients with severe comorbidities, or in resource-limited settings. Preoperative rehabilitation (prehabilitation) reduces bedridden time, enhances mobility, and improves postoperative outcomes for patients scheduled for hip arthroplasty due to femoral neck fractures. However, prehabilitation is hindered by insufficient pain control. The pericapsular nerve group (PENG) block provides effective analgesia while preserving motor function. We designed a study to assess the efficacy of PENG block in facilitating prehabilitation for patients with femoral neck fractures who are scheduled for hip arthroplasty. Methods This prospective randomized placebo-controlled double-blinded trial aims to enroll 100 patients with Garden 3 or 4 femoral neck fractures who are scheduled for hip arthroplasty. Participants will be randomly assigned to receive a PENG block with 0.375% ropivacaine (PENG group) or with normal saline (placebo group) before the initial prehabilitation session. The prehabilitation program comprises five items: Bed-sitting, Edge-sitting, Stand-up, Maintaining-standing, and Wheelchair-transfer, performed with the assistance of a single physical therapist. The primary outcome is the percentage of patients completing the entire prehabilitation program. Secondary outcomes during the initial prehabilitation session are the achievement of each program item and the Numerical Rating Scale (NRS) pain score. Other secondary outcomes include intraoperative bleeding amounts, thromboembolic events during postoperative day 0 to 7, postoperative 3-day cumulative Cumulated Ambulation Score (CAS), and discharge destination. The postoperative outcomes will be compared between subgroups of patients undergoing surgery within 48 h of admission and those undergoing surgery more than 48 h of admission. Discussion This is the first study aiming to assess the efficacy of PENG block in prehabilitation for patients with femoral neck fractures who are scheduled for hip arthroplasty. PENG block could be beneficial, especially for patients facing delayed surgery, providing a potential treatment option during the waiting period. Trial registration Japan Registry of Clinical Trials, jRCT1031220294, registered on August 26, 2022.